THE EFFECT OF USING REVIEW STRATEGY TO IMPROVE STUDENTS’ WRITING SKILL AT SMAN 18 MAKASSAR - Yokmeam Tiranda; Restu Januarty Hamid; Ulfah Syam (Lembaga Jurnal FKIP Universitas Bosowa, 2023)
Yokmeam Tiranda. 2023. The Effect of Using Review Strategy To Improve Students’ Writing Skill At SMAN 18 Makassar. Skripsi English Language Education Study Program, Faculty of Teacher Training and Education, Bosowa University. Supervised by Restu Januarty Hamid and Ulfah Syam.This study aimed to know the effect of using review strategy to improve student writing skill at SMAN 18 Makassar. This study used pre-experimental research one group pre-test and post-test. The population in this study was students of class XI IPA SMAN 18 Makassar. The writer took one class from the target population for the research.The sample to be used is class XI IPA 3, the number of samples is 30 students. Data obtained from writing test. The result of this study used inferential analysis of the t-test by SPSS v.16, which showed a signficant effect on the students’ mean score writing skill between the pretest and post-test. The average score of the students’ writing enhanced from 55.10 in the pretest to 88.90 in the posttest. The significance value calculated 0.000 is smaller than 0.05 (P-value = 0.000 < 0.05). Thus, it can be concluded that the review strategy is effect applied to improve students’ writing skill at SMAN 18 Makassar.